2015
DOI: 10.5812/ijem.31790
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Religion Involvement Predicts Subsequent Salivary Cortisol Levels Among Male But not Female Black Youth

Abstract: Background:Compared to Whites, Blacks are exposed to higher levels of chronic stress in the United States. As a result, major Black-White differences exist in the baseline and response of cortisol. Yet, the potential association between baseline religiosity and subsequent cortisol levels of Blacks are not known.Objectives:In the current study we aimed to determine the association between baseline religious behaviors and daytime salivary cortisol level among male and female Black youth.Materials and Methods:Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…For other R/S measures examined in relation to diurnal cortisol rhythms, no significant differences between the extent of religiosity, extent of spirituality, religious service attendance, non-theistic daily spiritual experiences, or theistic daily spiritual experiences, and diurnal cortisol rhythms were found. Our results with respect to religious service attendance and diurnal cortisol rhythms are similar to findings from two previous studies that found no evidence of an association between religious service attendance and cortisol levels measured during the day [ 47 , 48 ], but different from another recent study that observed an inverse association between frequent religious service attendance and mean cortisol level among a sample of 227 Black young adults, with six years of follow up [ 25 ]. In addition, our null findings with respect to assessing the association between the extent of religiosity or spirituality and diurnal cortisol rhythms are in contrast to four other studies that have documented a significant association between identifying as someone who is “very” religious or spiritual and lower cortisol levels [ 24 , 27 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 83%
“…For other R/S measures examined in relation to diurnal cortisol rhythms, no significant differences between the extent of religiosity, extent of spirituality, religious service attendance, non-theistic daily spiritual experiences, or theistic daily spiritual experiences, and diurnal cortisol rhythms were found. Our results with respect to religious service attendance and diurnal cortisol rhythms are similar to findings from two previous studies that found no evidence of an association between religious service attendance and cortisol levels measured during the day [ 47 , 48 ], but different from another recent study that observed an inverse association between frequent religious service attendance and mean cortisol level among a sample of 227 Black young adults, with six years of follow up [ 25 ]. In addition, our null findings with respect to assessing the association between the extent of religiosity or spirituality and diurnal cortisol rhythms are in contrast to four other studies that have documented a significant association between identifying as someone who is “very” religious or spiritual and lower cortisol levels [ 24 , 27 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 83%
“…Although they score comparatively lower than their female counterparts on various indices of faith (Taylor et al, 2004), Black men tend to embrace faith life (Smith et al, 1999), and believe that religion plays powerful roles in their lives and in their efforts to navigate life's challenges (Chung et al, 2014;Krause et al, 2002;Maliski et al, 2010;McFarland, 2010;Smith et al, 1999). Furthermore, evidence suggests that Black males accrue greater physical and mental health benefits from religious involvement than their female counterparts (Assari et al, 2015).…”
Section: Existential Well-being Spirituality and Pessimismmentioning
confidence: 99%
“…Differential effects of PEA are shown for race, [24][25][26][27][28] ethnicity, 23,[29][30][31] sexual orientation, 32 nativity, 22 place, 33 and sex. [34][35][36][37][38][39] In all these cases, parental education's gradient or threshold effect is found to vary across subgroups of children based on a demographic factor. 23,29,[40][41][42] This can be partly because social processes may interfere with some parts of society's ability to leverage the social resource (SEP) and turn them into tangible behavioral or health outcomes.…”
Section: Introductionmentioning
confidence: 98%